Prospects for multimodal imaging of biological tissues using fluorescence imaging. (February 2021) - Tuchina, D K; Meerovich, I G; Sindeeva, O A; Zherdeva, V V; Kazachkina, N I; Solov'ev, I D; Savitsky, A P; Bogdanov, A A; Tuchin, V V
Abstract: We investigate skin optical clearing in laboratory animals ex vivo and in vivo by means of low-molecular-weight paramagnetic contrast agents used in magnetic resonance imaging (MRI) and a radiopaque agent used in computed tomography (CT) to increase the sounding depth and image contrast in the methods of fluorescence laser imaging and optical coherence tomography (OCT). The diffusion coefficients of the MRI agents Gadovist ®, Magnevist ®, and Dotarem ®, which are widely used in medicine, and the Visipaque ® CT agent in ex vivo mouse skin, are determined from the collimated transmission spectra. MRI agents Gadovist ® and Magnevist ® provide the greatest optical clearing (optical transmission) of the skin, which allowed: 1) an almost 19-fold increase in transmission at 540 nm and a 7 – 8-fold increase in transmission in the NIR region from 750 to 900 nm; 2) a noticeable improvement in OCT images of skin architecture; and 3) a 5-fold increase in the ratio of fluorescence intensity to background using TagRFP-red fluorescent marker protein expressed in a tumour, after application to the skin of animals in vivo for 15 min. The obtained results are important for multimodal imaging of tumours, namely, when combining laser fluorescence and OCT methods with MRI and CT, since the contrast agents under study can simultaneously enhance the contrast of several imaging methods.